Decolourisation of reactive dyestuff using Fenton's reagent - Aris, Azmi; Sharratt, Paul N. (Faculty of Civil Engineering, UTM, 2005)
The behaviour of Fenton's Reagent (FR) system in decolourising Reactive Black 5 (RB5) was investigated. It was observed that the system is capable to decolourise 0.2 mM RB5 within a reasonable time with most decolourisation occurred in the first minute. The performance of the process is greatly affected by the reagent dosage. The best dosages of peroxide and Fe2+ were 7 mM and 1 mM, respectively. The best H202:Fe2+:dye molar ratio was 35:5:1. The dye was also found to enhance the decomposition of the peroxide. This suggests the possibility of Fe3+7Fe2+ `redox-recycled' as experienced in a Hamilton-like system favouring the use of FR process for the degradation of the dye.